Clinical Significance of MicroRNA-29a and MicroRNA-100 Gene Expression in Pediatric Acute Myeloid Leukemia. Issue 2 (March 2022) - Said, Fadwa; Tantawy, Marwa; Sayed, Ahmed; Ahmed, Sonia
Abstract : Aim: The aim of this study was to evaluate the diagnostic and prognostic performance of miRNA-29a and miRNA-100 in pediatric acute myeloid leukemia (AML). Patients and Methods: In all, 73 children with diagnosed pediatric AML (based on standard morphologic, cytochemical, cytogenetic, immunologic, and molecular workup, and the French-American British classification) admitted to Children's Cancer Hospital Egypt (CCHE-57357), and 9 healthy age-matched and sex-matched controls were recruited for a case-control study. Gene expression levels of miRNA-29a and miRNA-100 were assessed using real-time quantitative RT-PCR. Results: When diagnosed, patients had a significantly higher expression of miRNA-100 as against controls (median [range]: 12.99 [0.92-851.38] vs. 0.26 [0.03-2.67], P <0.001), with a significantly lower expression of miRNA-29a (2.08 [0.02-19.72] vs. 24.95 [15.48-42.54], P <0.001). Likewise, high-risk patients according to cytogenetic stratification had significantly higher miRNA-100 expression and lower miRNA-29a expression. Both miRNA-100 and miRNA-29a performed well as diagnostic markers of pediatric AML with an area under the curve of 0.977 (95% confidence interval [95% CI: 0.943-1.0]) and 0.994 (0.982-1.0) for miRNA-100 and miRNA-29a, respectively. Both miRNA-29a (odds ratio [95% CI]: 0.160 [0.054-0.474], P =0.001) and miRNA-100 (odds ratio [95% CI]: 1.997 [1.994-2.001], P =0.047) were identified as significant predictors of treatment response. Conclusion: The miRNA-29a and miRNA-100 expression may serve as diagnostic and prognostic markers in pediatric AML.